Proceedings of the 2014 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2014
DOI: 10.1145/2632048.2636070
|View full text |Cite
|
Sign up to set email alerts
|

Breaking boundaries

Abstract: People-nearby applications" (PNAs) are a form of ubiquitous computing that connect users based on their physical location data. One example is Grindr, a popular PNA that facilitates connections among gay and bisexual men. Adopting a uses and gratifications approach, we conducted two studies. In study one, 63 users reported motivations for Grindr use through open-ended descriptions. In study two, those descriptions were coded into 26 items that were completed by 525 Grindr users. Factor analysis revealed six us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 39 publications
5
36
0
3
Order By: Relevance
“…Several studies published in recent years have focused on the use of GSN apps among MSM with a particular focus on motivations for GSN app use (Grosskopf, LaVasseur, & Glaser, 2014; Van De Wiele & Tong, 2014), sexual risk behaviors (Beymer et al, 2014, Rice et al, 2012; Lehmiller & Ioerger, 2014; Winetrobe, Rice, Bauermeister, Petering, & Holloway, 2014), HIV testing (Rendina, Jimenez, Grov, Ventuneac, & Parsons, 2014), and the acceptability of varied HIV prevention strategies among users (Burrell et al, 2012; Holloway et al, 2014; Landovitz et al, 2013). While none of these studies have focused explicitly on substance use, several have reported substance use prevalence among users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies published in recent years have focused on the use of GSN apps among MSM with a particular focus on motivations for GSN app use (Grosskopf, LaVasseur, & Glaser, 2014; Van De Wiele & Tong, 2014), sexual risk behaviors (Beymer et al, 2014, Rice et al, 2012; Lehmiller & Ioerger, 2014; Winetrobe, Rice, Bauermeister, Petering, & Holloway, 2014), HIV testing (Rendina, Jimenez, Grov, Ventuneac, & Parsons, 2014), and the acceptability of varied HIV prevention strategies among users (Burrell et al, 2012; Holloway et al, 2014; Landovitz et al, 2013). While none of these studies have focused explicitly on substance use, several have reported substance use prevalence among users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has more than 3 million daily active users worldwide, who spend an average of 54 minutes interacting with the app each day [31]. App usage is primarily for finding hookups [61], but users also report usage for socialising, friendship, entertainment, dating, and gay community involvement [53,64]. In contrast to interventions which focus on promoting awareness, Grindr proposed implementing an explicit field for publicly reporting HIV status on user profiles, and the ability to filter users based on their status.…”
Section: Introductionmentioning
confidence: 99%
“…The anonymity afforded by the internet has made it an essential tool for queer individuals to connect with other queer people [19]. Historically, congregating in physical spaces has caused safety concerns for queer people., As a result, much social activity has now shifted online [22]. Feelings of anonymity are also crucial in the early stages of developing one's identity due to the commonly experienced fear of stigmatisation if one were to be discovered [10].…”
Section: Related Workmentioning
confidence: 99%
“…A range of dating apps, which we include in the scope of SNS, are increasingly becoming a popular space for queer people to interact. However, our review of the literature shows that Grindr, a location-based dating application for queer men, is the main app to have received attention from researchers [2,17,22]. While Grindr is often perceived as a place to find casual sex, many people use it in the hopes of finding social connections or romantic relations 18 Transgender [22].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation